ANALISIS PRODUKSI DAN PEMASARAN DALAM KERANGKA SUPPLY CHAIN MANAGEMENT JERUK KEPROK SOE DI KABUPATEN TIMOR TENGAH SELATAN - , Ir. Yusuf, MP, Prof. Dr. Ir. Masyhuri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to analyze factors affecting production and revenue, feasibility of farming, marketing of Jeruk Keprok Soe. It was also to examine factors of buying and factors affecting consumersâ demand in Jeruk Keprok Soe, as well as understanding the principles of Supply Chain Management in Jeruk Keprok Soe. The study was conducted in South Central Timor Regency. The data used were primary data from farmer respondents in South Central Timor Regency, sellers in South Central Timor and Kupang, preferences and consumersâ demand in Kupang and its surrounding and secondary data as supporting data from related organisation. Data analysis was Cobb-Douglas regression analysis of production function model, feasibility of farming (Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B / C Ratio), Break Event Point / BEP, marketing channels, marketing margins in Cobb-Douglas production regression model, marketing efficiency using simple regression, consumersâ attitudes using Fishbein model, consumersâ demand using simple regression and analysis of Supply Chain Management policies using qualitative analysis. The results showed that the production of Jeruk Keprok Soe was positively influenced by: insecticides, California porridge, labors, plant population, farming experience and formal education of farmers. Jeruk Keprok Soe farmers' income was positively influenced by: the price of organic fertilizer and insecticide, wage labors, plant population and farming experience. Jeruk Keprok Soe was worthwhile to produce using several approaches: (a) Net Present Value (NPV), (b) Net B / C ratio, (c) IRR. There are 4 types of Jeruk Keprok Soe marketing chain, i.e.: (i) farmers as sellers â end- consumers, (ii) farmers - retailers â endconsumers, (iii) sellers - end-consumers and (iv) farmers â sellers - retailers â endconsumers. Marketing margin was positively affected by prices at producer level, the number of stages and production volume. Characteristics considered in buying Jeruk Keprok Soe were as follows: taste, freshness, place of origin, ripeness, water content, color, consumer image, skin thickness and size. Attitudes and classification of consumersâ attitudes towards the characteristics of Jeruk Keprok Soe was quite good. Consumersâ demand of Jeruk Keprok Soe was positively influenced by the price of Jeruk Keprok Soe, prices of other Jeruk Keprok Soe, consumersâ incomes, taste, size and water content of Jeruk Keprok Soe. Jeruk Keprok Soe farm development in Supply Chain Management framework has not adopted the six principles of SCM.